Events In The Fergana Valley During The 1920s–1930s: Famine and Its Socio-Economic Significance - Baxodirovich, Nizomiddinov (Indonesian Journal Publisher, 2025)
In the 1920s and 1930s, the famine and socio-cultural changes in the Fergana Valley were the result of large-scale political and economic transformations. This article examines the causes and consequences of the famine and its impact on society and cultural life. The Soviet reforms, including collectivization policies, state centralization of food resources, and their effects on the socio-economic life of the region, are explored. The famine’s influence on people’s way of life, local customs, and the government’s political decisions in this regard are thoroughly analyzed. Based on archival documents and academic literature, conclusions are drawn about how the famine exacerbated the economic crisis in the Fergana Valley, sparked widespread discontent, and influenced the local social culture.